Ayatollah Ruhollah Khomeini and Forming Foreign Policy of Islamic Republic of Iran - E. G. Amirov (Научный диалог)
The author analyzes the influence of the ideas of Ruhollah Musavi Khomeini, the leader and founder of the Islamic revolution of 1979 in Iran, on the formation of the main directions and principles of Iranian foreign policy in the context of the first ten years of the Islamic state in Iran. Specific examples show the attitude of Ayatollah Khomeini to foreign policy issues in the years of the anti-Shah movement in Iran, as well as the final form of his system doctrine after the 1979 revolution. Considering in a comparative perspective the foreign policy priorities of the Shah and the Islamic regime, the author focuses on the metamorphoses of Iranian diplomacy of the 1980s. It is noted that the Islamic Republic has declared its priority the strengthening relations and cooperation with the Muslim world, as well as ideological, economic and military-political opposition to the West. At the same time, Khomeini’s pragmatic approach to practical politics is shown, which in many cases had serious differences with his theoretical ideas about the foreign policy of the Islamic Republic.